2024
DOI: 10.1039/d3ma00829k
|View full text |Cite
|
Sign up to set email alerts
|

Borophene nanomaterials: synthesis and applications in biosensors

Gourang Hari Gupta,
Shikha Kadakia,
Darshan Agiwal
et al.

Abstract: Borophene, is an allotropic form of boron that exists in different dimensional form from zero dimensional (0D) to three dimensional (3D) and have excellent property like high tensile strength, thermal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…This functionalization can enhance borophene’s ability to selectively interact with specific bioanalytes, improving its physical adsorption to the surface for biosensing applications. Borophene’s anisotropic nature, high electron mobility, and high electroactive surface area can further contribute to the development of highly selective and sensitive biosensors. , Recently, Gui et al synthesized metal–organic framework-based composites with boron nanosheets to develop electrochemical biosensors for different biomarkers. , Other studies have reported the synthesis of borophene nanocomposites with metals and various other active organic ligands, such as polyaniline and phthalocyanine, and used them as nonenzymatic electrochemical biosensors. …”
Section: Introductionmentioning
confidence: 99%
“…This functionalization can enhance borophene’s ability to selectively interact with specific bioanalytes, improving its physical adsorption to the surface for biosensing applications. Borophene’s anisotropic nature, high electron mobility, and high electroactive surface area can further contribute to the development of highly selective and sensitive biosensors. , Recently, Gui et al synthesized metal–organic framework-based composites with boron nanosheets to develop electrochemical biosensors for different biomarkers. , Other studies have reported the synthesis of borophene nanocomposites with metals and various other active organic ligands, such as polyaniline and phthalocyanine, and used them as nonenzymatic electrochemical biosensors. …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in 2022, an atomically well-defined borophene polymorph in a double-layer structure consisting of two covalently bonded α-phase layers of borophene was synthesized and exhibited greater stability compared to single-layer borophene. 27,28 This success raises the question of whether similar theoretical principles can be applied to design binary or multi-elemental 2D structures. In our previous study, we devised a novel binary 2D material of δ-Be 2 C, forming a double-layer structure with hepta-coordinated carbons.…”
mentioning
confidence: 99%